CYBERNETICS IN FUNCTION OF AMBITIOUS FUTURE OF AGRICULTURE - Todosijevic Lazovic, Snezana (Economics of Agriculture, 2020)
Cybernetics deals with basic laws of management, managing systems and systems that are being managed. It is about organization complex of different elements and mutual influences bonded in a system. That bond functions based on feedback, companies management evaluates information that are causing new commands to emerge which can correct work in accordance with delegated task. By mobilizing large number of scientific disciplines and ways, cybernetic has become a science of mutual regularity of management. Mathematical logic and theory of algorithms (base of digitalization) have benefited from cybernetics. Theory of recognition occurs. AI and isomorphism have happened that are characterized by equality of forms and it doesnt bypass agriculture, which is manifested through: ground analysis, choice of planting material, prescription for treatment and processing procedures, storage, transport and distribution. Robotization, IT, AI and digitalization make up symbiosis of action for achieving ambitious goals of agriculture.